2021
DOI: 10.1111/tbed.14343
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of an outbreak of bovine tuberculosis in a man‐made multi‐host species system: A call for action on wildlife in Brazil

Abstract: We report on a 15‐year‐long outbreak of bovine tuberculosis (bTB) in wildlife from a Brazilian safari park. A timeline of diagnostic events and whole‐genome sequencing (WGS) of 21 Mycobacterium bovis isolates from deer and llamas were analyzed. Accordingly, from 2003 to 2018, at least 16 animals, from eight species, died due to TB, which is likely an underestimated number. In three occasions since 2013, the deer presented positive tuberculin tests, leading to the park closure and culling of all deer. WGS indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
3
0
1
Order By: Relevance
“…Unlike the scarcity of infectious disease reports in free-ranging wild cervids in Latin America, in captive populations, there are epidemiological and pathological reports that confirm the susceptibility of native species in the region to livestock and zoonotic pathogens [5,37,[126][127][128]. In the present study, the same infectious agents that were detected in wild pudus were detected in captive pudus, except for Neospora caninum, which suggests that, in Chile, infectious diseases of wildlife under human care are the same as those of free-ranging individuals.…”
Section: Under-human-care Pudusmentioning
confidence: 99%
“…Unlike the scarcity of infectious disease reports in free-ranging wild cervids in Latin America, in captive populations, there are epidemiological and pathological reports that confirm the susceptibility of native species in the region to livestock and zoonotic pathogens [5,37,[126][127][128]. In the present study, the same infectious agents that were detected in wild pudus were detected in captive pudus, except for Neospora caninum, which suggests that, in Chile, infectious diseases of wildlife under human care are the same as those of free-ranging individuals.…”
Section: Under-human-care Pudusmentioning
confidence: 99%
“…Outputs are particularly compromised by homoplasy and are insufficient to gain insights into the roles exerted by different species in the multi-host system ( 22 , 23 ). Whole-genome sequencing (WGS) approaches can overcome these limitations, using single-nucleotide polymorphisms (SNPs) as reliable phylogenomic markers, identifying genetic population structures while linking to co-variables of interest, thus unraveling transmission drivers and routes ( 19 , 24 32 ). Global studies have identified five main clonal complexes, with three predominant in Europe: Eu1 is globally distributed, with an origin associated with the British Isles ( 33 ); Eu2 (lineage La1.7.1) is predominant in the Iberian Peninsula ( 33 ); Eu3 was recently shown to be predominant in Western Europe and East-Africa ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…few ecotypes are highly adapted to humans while others are more adapted to animals), virulence, and transmission capacity . In contrast, Mycobacterium bovis infects a broad range of animal species, with higher predominance in bovids, but can also cause disease in many wild animals with variable populational persistence LIMA et al, 2021). It is also the main pathogen of zoonotic TB in humans, but it is rarely transmitted between diseased individuals .…”
Section: Introductionmentioning
confidence: 99%